AMBIGUITAS HUKUM : PERATURAN KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET DAN TEKNOLOGI NO. 30 TAHUN 2021 - Sandiwan Putra Bintang Anugrah; Andyra Fathur Rizky; Ahcmad Maulana Rafit Arik (JOURNAL OF LAW AND NATION, 2024)
Cases of sexual violence in Indonesia continue to increase every year, not only among adults but also among teenagers, children and even toddlers. This phenomenon is a global problem that occurs in almost every country. In response to the increase in cases of sexual violence, the Ministry of Education and Culture issued Ministry of Education and Culture Regulation no. 30 of 2021 to prevent and handle sexual violence in the campus environment. Universities as educational institutions have a responsibility to create an environment free from violence in any form. The impact of sexual violence is very bad, so prevention and handling must be taken seriously. Patterns of sexual violence on campus can involve various parties, including students, lecturers and educational staff. The university formed a Sexual Violence Prevention and Handling Task Force to handle these cases and carry out outreach and counseling via social media. It is hoped that with these steps, the academic community will have a better understanding of preventing and handling sexual violence.